Penilaian Risiko Kecelakaan Kerja dengan Metode Job Safety Analysis dan Risk Assessment pada PT. Asia Pacific Fibers - Zidane, Ahmad; Nuraini, Umi (Fakultas Teknik Universitas Tulang Bawang, 2024)
Asia Pacific Fibers, Tbk Karawang is one of the factory facilities producing Polyester Chips and Synthetic Fibers which was previously called PT.Polysindo Eka Perkasa. PT. Asia Pacific Fibers is a public company operating in the textile sector and headquartered in Jakarta, Indonesia. The company also has standard procedures for dealing with emergency situations and providing appropriate personal protective equipment (PPE) to employees. The Occupational Health and Safety (OHS) system in a company should be considered. However, even though the company has implemented an OHS system, there are still many employees who violate it and lack awareness of work accidents that can occur. Therefore, this research aims to identify and assess potential work accidents and determine which potentials must be prioritized. The methods used in this research are job safety analysis (JSA) and risk assessment. The results of this research are that there are 2 potential work accidents in the minor/tolerate category, 3 in the moderate category, and 2 potential work accidents in the serious category and immediate prevention recommendations must be given. Keywords: Hazard, Job Safety Analysis, OHS, Risk Assessment